Design and Fabrication of a Compact SIW Diplexer in C-Band - N. Kiani; M. Afsahi (Iranian Journal of Electrical and Electronic Engineering, 2019)
In this paper, a compact 6.8/7.6 GHz diplexer is provided with the help of substrate integrated waveguide (SIW) structures. The use of this structure is for satellite communication systems. The designed diplexer includes a T-junction. In addition, our structure consists of two SIW filters of the type of bandpass. The relative bandwidth of the upper channel is 3.3% at the center frequency of 7.6 GHz and its lower channel is 3.7% at the center frequency of 6.8 GHz. The proposed diplexer offers a great benefit in terms of size decrease. In addition, it displays an optimal insertion loss. While giving the low return loss. Ultimately, the designed structure displays ideal rates of isolation and rejection. The diplexer incorporates a planar form and can be simply integrated with to the integrated circuits of the microwave. The insertion and return losses are 1.8 dB and 15d B in the lower band and they are 1.9 dB and 17 dB in the upper band. Simulations have been implemented with CST Microwave Studio. The Diplexer is completely built into a standard printed circuit board (PCB) procedure. A very favorable compromise is reached among the results of the construction and the measurement, which is the evidence of the proposed method.